Isolation and Partial Characterization of a New Moderate Thermophilic Albidovulum Sp. slm16 with Transaminase Activity from Deception Island, Antarctica - Blamey-Alegria, J (NLM (Medline), 2019)
BACKGROUND: A moderately thermophilic, slightly halophilic, aerobic, Gram-stain negative, bacterial strain, SLM16, was isolated from a mixed of seawater-sand-sediment sample collected from a coastal fumarole located in Whalers Bay, Deception Island, Antarctica. The aim was to screen for thermophilic microorganisms able to degrade primary amines and search for amine transaminase activity for potential industrial application. RESULTS: Identification and partial characterization of the microorganism SLM16 were carried out by means of morphological, physiological and biochemical tests along with molecular methods. Cells of strain SLM16 were non-motile irregular rods of 1.5-2.5 μm long and 0.3-0.45 μm wide. Growth occurred in the presence of 0.5-5.5% NaCl within temperature range of 35-55 °C and pH range of 5.5-9.5, respectively. The DNA G+C composition, estimated from ftsY gene, was 66% mol. Phylogenetic analysis using de 16S rRNA gene sequence showed that strain SLM16 belongs to the marine bacterial genus Albidovulum. CONCLUSION: Strain SLM16 is a moderate thermophilic Gram negative microorganisms which belongs to the marine bacterial genus Albidovulum and is closely related to Albidovulum inexpectatum species based on phylogenetic analysis. Additionally, amine-transaminase activity towards the arylaliphatic amine α-methylbenzylamine was detected.